Characterization and Application of HCl-Activated LTA Zeolite from Lampung Natural Zeolite (LNZ) for Bioethanol Purification - Ginting, Simparmin Br; Wardono, Herry; Islamia, Ulfa; ., Darmansyah (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Lynde Type-A (LTA) zeolite as being molecular sieve and hydrophilic zeolite is used to dehydrate water in the purification of bioethanol. LTA zeolite from LNZ has a small surface area of 29,62 m2/g. Adding HCl activators to LTA Zeolite from LNZ was carried out to increase the surface area of LTA zeolite. The activation of LTA zeolite was carried through in a closed erlemeyer with various HCl concentration: 10% w/w, 15 % w/w, and 20% w/w and the ratio acid/LTA zeolite was 10 ml: 1 gram. The XRD analysis showed that the structure of LTA zeolite activated does not change despite the process of activation, and the highest percentage of crystallinity was obtained at 68.25% wt by concentration of HCl at 20 % w/w. The result of XRF analysis showed that the highest of impurity removal and the highest of decreasing ratio of Si/Al was in the LTA zeolite activated by HCl 20% w/w. The result of BET analysis showed the largest surface area at 45.67 m2/g obtained by adding 10% w/w of HCl activator, which was 45.67 m2/g, and the size of zeolites pore volume was 0.027 cc/g. The result performance of LTA zeolite activated obtained the highest purity of bioethanol by 99.74 % v/v at HCl concentration 20% w/w.